(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides some thoughts on the proclamation of the new Uzbekistan as a social State, the creation of conditions for a decent life for every citizen, the distribution of available resources on the basis of the principles of social justice, the prevention of the development of strong stratification in society, and the provision of quality education and medicine even for the most vulnerable segments of the population.